The selection criteria of Islamic bank customers among IIUM students : empirical analysis and implication on marketing - Rustam, Mohammed Gulamali (2009)
The aim of this study is to examine the bank selection criteria being employed by the students in Malaysia. A total of 300 undergraduate students of the International Islamic University Malaysia, main campus were selected as a sample for the study. The choice of students of undergraduate level reflects the average age of young customers between 19 to 25 years. My examination relied on 5 selection factors extracted from relevant literature, personal experience and interviews with some bank officials and students. This study is also designed to examine the CLlStomer'!; knowledge in Islamic banking and the factors considered in the selection process of Islamic banks by demographic group and socio-economic characteristics. The data collected from the study is analysed by SPSS Program (version 13), mean factor analysis and then factor analysis to enhance the quality of result by the empirical survey. Previous literature suggests that factors such as banks' strong Islamic reputation as well as better financial return and banking services are to be among the leading factors in the selection criteria of the respective Islamic bank. The main implication of this study is to help marketing executives in the Islamic banks to plan better marketing strategies that would attract new customers as well as retain the existing ones in today's highly competitive environment dominating the financial industry.